Hubungan Antara Self Compassion Dengan Resiliensi Pada Warga Binaan Perempuan - Anisa Fitri Nurjanah; Alfin Miftahul Khairi (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
This research aims to determine the relationship between self-compassion and resilience in female inmates at the Surakarta Class I State Detention Center. The hypothesis in this research is that there is a relationship between self-compassion and resilience in female inmates who are serving a period of detention at the Surakarta Class I State Detention Center. This research uses a correlational quantitative approach. The subjects in this research were 38 female inmates at the Surakarta Class I State Detention Center. The data collection method in this research uses a Likert scale questionnaire which consists of two scales, namely the self-compassion scale and the resilience scale. Data analysis was carried out using Pearson correlation analysis to obtain a correlation coefficient of 0.496 and a significance value of 0.002 (p<0.05). This means that the higher the self-compassion of female inmates, the higher their resilience, conversely, the lower the self-compassion of female inmates, the lower their resilience. The results of this research show that there is a relationship between self-compassion and resilience in female inmates at the Surakarta Class I State Detention Center.